2005
DOI: 10.1172/jci25083
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 iodothyronine deiodinase is the major source of plasma T3 in euthyroid humans

Abstract: The relative roles of the types 1 and 2 iodothyronine deiodinases (D1 and D2) in extrathyroidal 3,5,3′-triiodothyronine (T 3 ) production in humans are unknown. We calculated the rate of thyroxine (T 4 ) to T 3 conversion by intact cells transiently expressing D1 or D2 at low (2 pM), normal (20 pM), and high (200 pM) free T 4 concentrations. Deiodinase activities were then assayed in cell sonicates. The ratio of T 3 production in cell sonicates (catalytic efficiency) was multiplied by the tissue activities rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(91 citation statements)
references
References 39 publications
2
84
0
Order By: Relevance
“…Maia et al (21) estimated that D2 is the major contributor of extrathyroidal T 3 production in euthyroid subjects, and peripheral T 3 production may switch from D2 to D1 dependency in thyrotoxic patients, since the D2 activity decreases due to the posttranslational substrate-induced inactivation of D2 (20,21). In this study, since the serum FT 4 level in the patients with T 3 -P-GD was within the normal range, we considered that D2-generated T 3 mainly contributes to the extrathyroidal T 3 production in the patients with T 3 -P-GD.…”
Section: Discussionmentioning
confidence: 99%
“…Maia et al (21) estimated that D2 is the major contributor of extrathyroidal T 3 production in euthyroid subjects, and peripheral T 3 production may switch from D2 to D1 dependency in thyrotoxic patients, since the D2 activity decreases due to the posttranslational substrate-induced inactivation of D2 (20,21). In this study, since the serum FT 4 level in the patients with T 3 -P-GD was within the normal range, we considered that D2-generated T 3 mainly contributes to the extrathyroidal T 3 production in the patients with T 3 -P-GD.…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of T3, which is considered to be the biologically active form of thyroid hormones, derives from peripheral conversion of the prohormone T4 via a reaction catalyzed by 5′‐monodeiodinases in organs such as the liver, kidney, and skeletal muscle 25, 26. It has been reported that a decrease in 5′‐monodeiodination leads to low serum T3 concentration in patients with any severe systemic illness, including acute myocardial infarction,27 and chronic heart failure 8.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, it was postulated that SM could participate in the regulation of serum T 3 levels since SM is wildly distributed and has a large mass (Maia et al 2005). However, global D2KO mice have normal levels of T 3 and increased levels of T 4 and TSH (Schneider et al 2001).…”
Section: Thyroid Hormone and Skeletal Muscle Physiologymentioning
confidence: 99%